As narrativas judaico-cristãs sobre o martirológio ashkenazi medieval (sécs. XI e XII) : construção e ressignificação do Kidush haShem nas crônicas hebraicas e latinas - Souza, Karla Constancio de (2018)
In this study we discuss the influences of the anti-Jewish massacres during the First Crusade (1096), in the cultural and religious transformation’s process of the Ashkenazim communities of the Rhineland in the Holy Roman Empire: Mainz, Cologne, Speyer, Worms, Trier, Metz and Regensburg. Such events represented a milestone for Judaism, because they led to great consequences in the Ashkenazi interpretation of the fundamental precepts of religion. The culmination of this cultural confluence between Christians and Jews occurred from the moment in which religious discourses of both were interwoven, originating a new conception of the Jewish religious practice of the ritual suicide, namely, Kidush HaShem. To elucidate our main objective, this work discusses the legacy of the cultural convergence between Jewish and Christian traditions and their implications for the medieval Judaism, as for the Christianity itself, which, at that time, was still struggling for assertion within the logic of power in medieval society. A possible consequence of this cultural convergence to Christianity was a process of inversion, that is, the clerical sectors of the Church, counting on popular adherence, may have developed from the Jewish martyrdom the notion of ritual crime, and later the libels of blood, in other words, accusations against the Jews, which appeared systematically between the twelfth and thirteenth centuries, from the events of the Crusades, even transposing this time-cut into a long-lasting process, with its last documented cases in Czarist Russia, already in the nineteenth's end. In order to develop our aim and to prove our hypotheses we will use as sources the set of Hebrew chronicles, written approximately between the end of the eleventh and the middle of the twelfth century, by three different authors - Rabbi Solomon Bar Samson, Rabbi Eliezer Bar Nathan, and the Mainz Anonymous - as well as a Latin texts’ pleiad, of clerics who described or commented the First Crusade’s massacres, and others who later reported on ritual crimes. For instance, we quote two chronicles written contemporaneous with the massacres of 1096, written by the monks Bernold of St. Blasien and Frutolf of Michelsberg, and another written between the years 1125 and 1150 by the cleric and medieval chronicler Alberto of Aachen. From these primary documents’ study, in the light of Discourse Analysis proposed by the Russian-French school, also called enunciative basis, we have made a sociocultural approach to the representations from the various narrative constructions about the events, focusing the discursive conflict regarding the Jewish question within the spheres which made up the clergy. In our opinion, the discursive conflict seems to arise around the cultural circularity in two spheres: first, in the two clerical spheres that defended or opposed violence against Jews and forced baptisms, respectively represented by sectors of the lower and upper clerical hierarchies; and in the second instance, in the mutual religious and cultural influence, as well as in the identities and alterities’ demarcation proper to the relations between Judaism and Christianity in the Central Middle Ages